Enhancing the Solar Still Performance Using Nanofluid-Based Volumetric Absorption Solar Collector and Solar Pond: An Experimental Investigation - Singh, Jagteshwar (My University, 2023)
The aim of the present research work is not only to enhance the diurnal distillate output but also to generate nocturnal distillate and, in turn, enhance the performance of the solar still. In the present work, a novel nanofluid-based volumetric absorption solar collector (NBVASC) has been employed for efficiently harnessing the solar energy and supplying the same to solar still during sunshine hours for improving its diurnal production rate. A convective solar pond has also been used for supplying the stored sensible thermal energy to the basin of the solar still via heat exchangers during the non-sunshine period to produce the nocturnal distillate, which makes the system a ‘round-the-clock’ unit to produce potable water. The research work was done in a proper sequence and hence the complete research was done in three phases. In the study’s first phase, a novel nanofluid-based volumetric absorption solar collector (NBVASC) was fabricated to provide supplementary thermal energy to the modified solar still during sunshine hours. It was fabricated by constructing a shallow container, filling it with nanofluid and covering its top surface with two closely spaced transparent glass covers. The base and sidewalls of the solar collector have been insulated with polyurethane foam to reduce the thermal losses to the surroundings. Further, this foam was covered with a 1mm thick galvanized iron sheet to protect this insulation foam from weather conditions. A serpentine type of copper pipe heat exchanger (circulating ethylene glycol-based water-soluble heat transfer fluid, using a 12V DC pump having a rated power of 19 W) was also placed within the NBVASC to exchange the absorbed thermal energy from the solar collector to the water in the still. The NBVASC was filled with nanofluid, which was prepared by using a small amount of used engine oil acquired from a four-stroke diesel engine. After filtering the resin, sludge etc., with a cotton cloth, the filtered oil was then again refined with 0.7μm filter paper. The filtered oil was then mixed with paraffin oil (followed by 30 minutes of ultra-sonication in a bath-type ultra-sonicator), consequently forming nanofluids of different concentrations (1.25mlL-1, 2.5mlL-1, and 5mlL-1). In the study’s second phase, the fabricated NBVASC was coupled with the solar still to evaluate its impact on the performance of the modified solar still compared to the conventional solar still under identical outdoor conditions. The experiments were done on the modified still [MS] (CSASC- and NBVASC-coupled solar stills) and the conventional still at the same time for a number of days through the period from March to July 2020. In this phase, the optimum nanoparticle concentration that should be employed in the NBVASC for obtaining maximum distillate output was also identified. It was found that the solar still coupled with NBVASC (at optimum nanoparticle concentration of 1.25mlL-1) performed better than the solar still coupled with paraffin oil-based conventional surface absorption-based solar collector (CSASC), suggesting that harvesting solar energy through volumetric absorption by nanofluids is more efficient and effective. The distillate productivity and efficiency of the modified still coupled with NBVASC (1.25 mlL-1) were found to be 75.3 % and 66.9 % more than the conventional still. A significant amount of night distillate was obtained from the modified solar still (MS) coupled with NBVASC owing to the large quantity of thermal energy stored in the basin water at the end of the sunshine of the day. The night distillate produced by the modified still was found to be 33.9% higher than the conventional still. In the third and final phase of the study, the solar still was tested for round-the-clock distillate production by integrating it with NBVASC during sunshine hours and with the solar pond during non-sunshine hours (integrated solar still). The thermal energy harnessed by the NBVASC was supplied continuously from 9:00 am to 6:00 pm, whereas the thermal energy stored in the solar pond was supplied during night hours (1:00 am to 4:00 am). Floating wicks were also placed in the basin of the integrated still to enhance the evaporation rates and hence improving the overall distillate and efficiency of the still. Economic analysis and the payback period were also calculated, which can be used to carry out commercial feasibility studies before the installation of similar types of solar desalination units in any part of the world. The integrated solar stills performed better than conventional still in all the experiments when coupled with the solar collector (9 am to 6 pm) and solar pond (1 am to 4 am), whether with or without wicks. The integrated solar still without wicks, when coupled with a paraffin oil-based surface absorption solar collector during sunshine hours and with a solar pond during the night, showed an increase of 44.8% and 33.6% over conventional solar still in productivity and efficiency, respectively. The integrated solar still with wicks, when coupled with the paraffin oil-based solar collector during sunshine hours and with solar pond during the night, showed an increase of 74.3% and 50.2% over conventional solar still in productivity and efficiency, respectively. The integrated solar still without wicks, when coupled with nanofluid (1.25 mlL-1) based volumetrically absorbing solar collector (NBVASC) during sunshine hours and with solar pond during night hours, showed an increase of 64.9% and 66.4% over conventional solar still in productivity and efficiency, respectively. The integrated solar still with wicks, when coupled with nanofluid (1.25 mlL-1) based volumetric absorption solar collector (NBVASC) during sunshine hours and with solar pond during night hours, showed an increase of 111.1% and 89.4% over conventional solar still in productivity and efficiency, respectively. A considerable amount of night distillate (after 1 am) was produced by integrated solar stills (with and without wicks) due to the coupling of integrated stills with the solar pond at night; there was a maximum increase of 268.9% in productivity compared to conventional still when integrated still has wicks in its basin. Manufacturing cost has increased by 59.1%, whereas distillate production cost decreased by 32.5% relative to conventional still. Exergy efficiency was 3.40% when wicks were used in the basin of integrated solar still coupled with NBVASC, and conventional still had the lowest with a value of 1.48%. The typical winter and summer day distillate produced by the modified stills coupled with NBVASC and the solar pond was found to be 2.05 L/m2/day and 4.62 L/m2/day, respectively. The diurnal and nocturnal distillate produced during summer experiments was 144.02% and 64.52% higher than in winter.
Keywords: Solar distillation; Solar still; Solar collector; Nanofluid; Solar Pond